2013
DOI: 10.1111/nuf.12015
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Student Resilience: A Concept Clarification

Abstract: The clarification of the concept will assist nurse researchers and nurse educators in developing interventions and educational strategies aimed at fostering resilience in nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 21 publications
3
163
0
12
Order By: Relevance
“…Protective factors come in many forms, including coping mechanisms, peer and family support, social connectedness, positive role modeling and mentorship, and intellectual stimulation. 29,45,46,71,72 Based on the concept of protective or "replenishing" factors, Jackson and colleagues recommended five self-development strategies to build resilience: building positive nurturing professional relationships and networks, maintaining positivity, developing emotional insight, achieving life balance and spirituality, and becoming more reflective. 64 It is in these areas of developing protective and replenishing factors in which school counselors may play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective factors come in many forms, including coping mechanisms, peer and family support, social connectedness, positive role modeling and mentorship, and intellectual stimulation. 29,45,46,71,72 Based on the concept of protective or "replenishing" factors, Jackson and colleagues recommended five self-development strategies to build resilience: building positive nurturing professional relationships and networks, maintaining positivity, developing emotional insight, achieving life balance and spirituality, and becoming more reflective. 64 It is in these areas of developing protective and replenishing factors in which school counselors may play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…29 Likewise, in a selective review of resilience literature, Stephens proposed a model of resilience in which protective factors were necessary to balance against student stressors. 46 Longenecker and colleagues discuss resilience themes that they believe are necessary curricular components in medical school including: hardship is an opportunity for growth, team work strengthens resilience, adaptability is more important than hardiness, and lifelong learning must be applied. 47 Through an integrated qualitative review, Milne and colleagues found that cultural, financial, and academic support were necessary components for resilience in indigenous nursing students.…”
mentioning
confidence: 99%
“…described resilience as strategies used by students to remain and succeed in the program, which denotes that resilience is a process. Stephens (2013), in her concept clarification of the resilience of nursing students, described resilience as a process of applying personal protective factors in coping with adversities. An intervention study that suggests resilience as a process was that of in which she investigated the effects of a 4-week educational program on resilience.…”
Section: Resilience Is Conceptualized As a Trait Or Processmentioning
confidence: 99%
“…Stephens' study was also based on her concept clarification of resilience as a process that can be learned and taught. In summary, the conceptualization of resilience as a process suggests resilience as a dynamic and changeable phenomenon involving growth and development (Carroll, 2011;Stephens, 2013).…”
Section: Resilience Is Conceptualized As a Trait Or Processmentioning
confidence: 99%
“…이러한 때 언어폭력 상황 등 다양한 스트레스에 직 면해 이겨낼 수 있는 힘이 회복탄력성이다 [14]. 회복탄력 성이 높으면 힘든 스트레스 상황을 잘 이겨내고 실습 상 황에 잘 적응할 수 있는 능력과 안녕이 증진된다 [14,15]. …”
Section: 서론unclassified